Variations in the price of foods and nutrients in the UK - Ian Crawford (Institute for Fiscal Studies (IFS), 2003)
This paper investigates the patterns and extent of differences in the prices paid for foods, and for the nutrients they contain, amongst households in the UK. The data used are from the National Food Survey and are unit prices, quantities purchased and nutrient conversion factors for each food. The paper first describes the circumstances under which ratios of unit prices are exact measures of cross section price variation. It also discusses a nonparametric method of recovering the underlying prices of nutrients under the maintined assumption that households have rational preferences over the nutritional characteristics of foods. It then uses these data to describe patterns in the variation of the price of food and nutrients with repect to household and regional characteristics.
Keywords: 330; Nahrungsmittelpreis; Volatilität; Großbritannien